2005
DOI: 10.4103/0019-5545.55941
|View full text |Cite
|
Sign up to set email alerts
|

Family support group in psychosocial rehabilitation

Abstract: Background:Support groups for families of persons with mental illness are emerging as significant components in psychosocial rehabilitation programmes.Aim:To ascertain the expectations of family members who attend family support group meetings and to find out the efficacy of such programmes.Methods:The data were collected from support group members using a semi-structured interview schedule. The study sample (n=20) was drawn from family members who attended the support group meetings regularly for a minimum pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 5 publications
2
6
0
Order By: Relevance
“…[161] Moreover, certain advantages of this kind of group were noted e.g. feeling of togetherness (25%), skills in dealing with the patient at home (20%), emotional support (15%), improvement in relationship with the patient (15%), understanding the problem (15%), reduction in fear and anxiety (10%).…”
Section: Role Of Family In the Management Of Psychiatric Patients: Prmentioning
confidence: 99%
See 1 more Smart Citation
“…[161] Moreover, certain advantages of this kind of group were noted e.g. feeling of togetherness (25%), skills in dealing with the patient at home (20%), emotional support (15%), improvement in relationship with the patient (15%), understanding the problem (15%), reduction in fear and anxiety (10%).…”
Section: Role Of Family In the Management Of Psychiatric Patients: Prmentioning
confidence: 99%
“…A study exploring the role of family support group in psychosocial rehabilitation of mentally ill patients found that family members with a higher level of education are likely to join support groups. [ 161 ] Moreover, certain advantages of this kind of group were noted e.g. feeling of togetherness (25%), skills in dealing with the patient at home (20%), emotional support (15%), improvement in relationship with the patient (15%), understanding the problem (15%), reduction in fear and anxiety (10%).…”
Section: Role Of Family In the Management Of Psychiatric Patients: Prmentioning
confidence: 99%
“…While most studies evaluating support groups for dementia are from the West, there are studies from Iran (Javadpour et al, 2008) and Taiwan (Chu et al, 2011) showing improved caregiver well-being. In India, support groups have been used for caregivers of people living with stroke (Malini, 2015) and those with mental illnesses (Ponnuchamy et al, 2005). To our knowledge, there are no published studies on evaluating a support group for dementia in India.…”
Section: Introductionmentioning
confidence: 99%
“…Ponnuchamy et al .,[ 11 ] examined the role of family support groups in psychosocial rehabilitation. They observed that members attending support group meetings, expected to get more information about the illness, to develop skills to cope with problems at home, and to learn skills to deal with the ill person.…”
Section: Introductionmentioning
confidence: 99%